MENINGKATKAN SELF EFFICACY PADA ANAK MULTIKEKHUSUSAN TUNADAKSA DAN TUNAGRAHITA SDLB PANCABAKTI KEC. WONOASRI MADIUN - Dian Agestingsih; Mutin Kartika Dewi; Suprihadi; Heny Sulistyo Rini; Retno Saraswati; Sulasih; Anna Tridiyanto; Endang Pudjiastuti Sartinah; Murtadlo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe and improve self-efficacy in children with multiple physical and mental disabilities at SLB Panca Bakti Wonoasri. The background of the problem raised is the challenges faced by children with special needs in the learning process, especially in terms of participation and understanding of the material. The method used in this study is a descriptive qualitative approach, with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the use of basic number flash card media significantly improves the cognitive abilities and self-confidence of children with physical disabilities and mental disabilities in understanding basic number concepts.